Schneider's introduction to public health - Kruger, Jessica; Moralez, Andy; Siqueira, C. Eduardo (Carlos Eduardo), 1955-; Schneider, Mary-Jane, 1939-. (Burlington, MA : Jones & Bartlett Learning, 2026)
Offering a thorough, accessible and lively overview of public health for students new to the field, Schneider's Introduction to Public Health offers a broad reaching, practical framework for understanding the forces and organizations of public health today. Through engaging, nontechnical language, illustrative real world examples, and the current political, economic, and cultural news of the day, students gain a clear understanding of the scope of today's public health problems and possible solutions.Building on Schneider's engaging and easy-to-read narrative approach, new author team Kruger, Moralez, and Siqueira draw on their diverse perspectives for the Seventh Edition to bring a greater focus on the social determinants of health, ecological approach, and life course experiences as a framework to understand public health in the 21st century. Key Features Updated statistics and information in every chapter illustrate the current state of public health. Streamlined organization to better align with a traditional 16-week semester course. New chapters addressing the COVID-19 pandemic, climate change, and mental health. New chapter on research methods, that includes qualitative data. Timely examples, including links to videos and websites, cover public health issues discussed in the text. Alignment with Council on Education for Public Health (CEPH) criteria for undergraduate public health--
Public Health : Science, Politics, and Prevention -- The Drivers of Health -- Health Across the Lifespan -- Government Influence and Responsibilities -- Public Health Research Methods -- The Role of Statistics and Data in Public Health -- Infectious Diseases -- COVID-19 : Experiencing and Learning from a Global Pandemic -- The Science and Principles of Epidemiology -- Genetic and Chronic Diseases -- Behavioral Contributors to Disease Risk -- Public Health Approaches to Mental Health -- A Clean Environment : The Basis of Public Health -- Climate Change: The Most Important Public Health Challenge of the 21st Century? -- Regulations that Impact Health -- The U.S. Medical System as a Public Health Problem -- The Future of Public Health.
Preceded by Introduction to public health / Mary-Jane Schneider with Henry S. Schneider ; drawings by Henry Schneider. Sixth Edition. 2021.
Includes bibliographical references and index.
Keywords: Public health; Public Health; Public Health Practice; MEDICAL / Public Health